SMS Controlled Unmanned Ground Vehicle - Biswas, Tanmoy; Goswami, Arup Kr; Pal, Manas; Naskar, Saptarshi (International Journal of Computer Sciences and Engineering, 2018)
An unmanned ground vehicle (UGV) is a vehicle that operates on the ground without an onboard human presence. UGVs can be used for many applications where it may be extremely dangerous, impossible, inconvenient, and unreachable by human operators. The UGV is equipped with a set of sensors to monitor the environment, and then it can take an autonomous decision or pass the sensory information to a human operator at a different location who will control the vehicle through wireless or wired communication channel. Study and implementation of various controlling techniques for Unmanned Ground Vehicle are our primary objective. Most of the techniques presently under use are extremely complex and costly as they require high bandwidth communication channel and complex hardware. We have used Short Messaging Service (SMS) to control the UGV, which eliminates the use of high bandwidth channels, costly mobile devices and internet or data connection network. The UGV will be continuously under the supervisory control of an operator till it is under the area covered by the GSM/GPRS mobile network. SMS would be sent through the mobile phone to the UGV housing a GSM module and an Arduino UNO. The SMS will be decoded and a set of signals corresponding to those SMS will be generated and sent to the controlling circuit of the vehicle. Entire experiment was carried out using Arduino UNO, GSM module SIM900A, Motor control driver unit based on L293D, geared DC motors, Aluminium based vehicle chassis, 9V DC batteries and a valid SIM card with enabled SMS facility.